Study on some blood biochemical parameters in postpartum crossbred cows treated with GnRH and PGF2alpha - SHESHAPPA, H; HONNAPPAGOL, S S; TANDLE, M K; AMANULLAH, MOHD (The Indian Journal of Animal Reproduction, 2023)
The levels of various blood biochemical parameters viz. plasma calcium, inorganic phosphorous and total protein were marginally higher in the GnRH and GnRH + PGF 2alpha . treated groups than the control. The Acetone level during the early postpartum period, however, was lower in treated than control group indicating beneficial effect of treatment..